1976
DOI: 10.1037/0278-7393.2.5.509
|View full text |Cite
|
Sign up to set email alerts
|

Short-term conceptual memory for pictures.

Abstract: Three converging procedures were used to determine whether pictures presented in a rapid sequence at rates comparable to eye fixations are understood and then quickly forgotten. In two experiments, sequences of 16 color photographs were presented at rates of 113, 167, 250, or 333 msec per picture. In one group, subjects were given an immediate test of recognition memory for the pictures and in other groups they searched for a target picture. Even when the target had only been specified by a title (e..g., a boa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

52
857
7
13

Year Published

1988
1988
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 824 publications
(929 citation statements)
references
References 22 publications
52
857
7
13
Order By: Relevance
“…In addition, in all three experiments, BE occurred for pictures that appeared in serial positions 1 and 2, suggesting that conceptual masking-the immediate onset of new, meaningful visual information-does not eliminate boundary extension (Intraub, 1984(Intraub, , 1999Potter, 1976Potter, , 1999.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In addition, in all three experiments, BE occurred for pictures that appeared in serial positions 1 and 2, suggesting that conceptual masking-the immediate onset of new, meaningful visual information-does not eliminate boundary extension (Intraub, 1984(Intraub, , 1999Potter, 1976Potter, , 1999.…”
Section: Discussionmentioning
confidence: 91%
“…It revealed no main effect of the masked interval's duration, F(3, 140) = 1.16, n.s., no effect of serial position, F < 1, and no interaction, F < 1. The lack of a serial position effect shows that the onset of new meaningful pictures during RSVP did not disrupt incorporation of the extrapolated region into the spatial representation of the scenes-that is, there was no effect of conceptual masking (Intraub, 1984;Potter, 1976). Figure 3 (right panel) shows the mean boundary rating as a function of the spatial location of the test picture for each masked interval (collapsed over serial position).…”
Section: Critical CC Trials: Targets and Test Pictures Are Identical mentioning
confidence: 99%
See 1 more Smart Citation
“…Even when many different visual stimuli are presented in very rapid sequence, they can be identified and their meaning extracted (Thorpe et al, 1996, Potter 1975. However, entry of this information into awareness appears to be a much slower process that can easily be overloaded (Potter, 1976). This serial, capacity-limited process can be dissociated from the more parallel processes that subserve recognition (Marcel, 1983).…”
Section: Neural-cognitive Basis Of the Nucleusmentioning
confidence: 99%
“…However, this depiction does not account for all situations of recognition. Scenes are often recognized very quickly, in a single glance-in fact, as fast as a single component object (Biederman, Mezzanotte, & Rabinowitz, 1982;Friedman, 1979;Intraub, 1997;Potter, 1976). Under these conditions, it has been shown that visual information could mediate scene recognition without the prior and necessary recognition of component objects (Schyns & Oliva, 1994).…”
mentioning
confidence: 99%